6 - Univers discursif et réforme des télécommunications : étude comparée du Sénégal et de l’Afrique du Sud - Oumar Kane, (Africa Media Review, 2008)
With the communication utopia (Breton 1997) claiming more ground, and through transparency it theoretically guarantees, communication has now become invested with the power to enhance societal life. We are not concerned, in this regard, with inter-subjective communication, as exemplified in the Greek agora or the African palaver tree models (Diagne 2006). Progressively, views sympathetic to the liberalisation of the telecommunication sector have emerged, leading to a widespread deregulation of this sector at global level. As early as 1984, the Maitland Committee set up by the International Telecommunications Organisation carried out an audit of the telecommunication infrastructures of Africa and as it turned out, the situation was particularly desperate throughout the continent. As a result, the development of the telecommunication sector has been perceived as the missing link between the countries of the South and those of the North. This paper seeks to highlight the circumstances that led to the emergence of both logical thinking and the resulting series of changes that occurred in the telecommunication sector. Special attention is paid to the external as well as exclusively national factors that determined the conception and the implementation of a structural reform of the telecommunication sector in African countries. This study uses a comparative approach and is based on a case study and secondary data obtained from the review of relevant literature. It focuses on two African countries, Senegal and South Africa, which contrast markedly in terms of language, cultural area, demography as well as colonial heritage. In spite of the surface differences, the comparative analysis of the major steps in the reform of their telecommunication sectors suggests, paradoxically, a parallel evolution of the said process in the two countries.